Albinismo con disminución visual y fotofobia en paciente masculino 34 años. - Estrella Cevallos, María Del Carmen (2023)
The optometrist must be prepared to address various clinical cases in professional practice. In the present clinical case, we have a 34-year-old male patient with albinism, this condition has been little studied. At the time of consultation, the patient presents decreased visual acuity and photophobia, and several tests are planned. The final diagnosis was high myopia and mild astigmatism, a diagnosis of photophobia was confirmed. Lenses with photochromic and blueblock protection are prescribed, as well as regular monitoring to detect any anomaly that may affect the patient's ergonomics. The importance of the optometrist professional as the first line of care is highlighted; in cases of albinism, it is necessary to implement measures that contribute to improving the patient's quality of life.